1987
DOI: 10.1590/s0006-87051987000200013
|View full text |Cite
|
Sign up to set email alerts
|

Germinação das sementes de marmelo: meios e períodos de estratificação e processos de preparo

Abstract: Dois experimentos foram conduzidos no sentido de se obter maior conhecimento das sementes de marmelo, como subsídios essenciais ao melhoramento genético dessa frutífera e à obtenção de porta-enxertos de pés francos para a pereira, a nespereira e o próprio marmeleiro. Os aspectos focalizados e as respostas obtidas foram: (a) Meios e períodos de estratificação. A estratificação úmida, a baixa temperatura (5 a 10°C) foi indispensável à quebra de dormência das variedades pesquisadas, Portugal e Smyrna. As sementes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…High loss of quince seedlings from the Cydonia genus in the emergency phase was caused due to the high damping-off occurrence (Campo Dall'Orto et al, 1987), what was not observed for the 'Japonês', but noticed for the other cultivars. Possibly, it can be one of the causes of the superiority of 'Japonês'.…”
mentioning
confidence: 74%
“…High loss of quince seedlings from the Cydonia genus in the emergency phase was caused due to the high damping-off occurrence (Campo Dall'Orto et al, 1987), what was not observed for the 'Japonês', but noticed for the other cultivars. Possibly, it can be one of the causes of the superiority of 'Japonês'.…”
mentioning
confidence: 74%